Application of the principles of Maqasid Shari‘ah in administration of the Islamic countries - Mohd Nor, Amir Husin; Alias, Muhammad Nazir; Samsudin, Mohd Adib; Omar, Anwar Fakri; Ibrahim, Ibnor Azli; Laluddin, Hayatullah; El-Seoudi, Abdel Wadoud Moustafa Moursi; Muhammad Husni, Ahmad; Abdul Manap, Norhoneydayatie (American-Eurasian Network for Scientific Information (AENSI), 2012)
Maqasid shari‘ah or objectives of Islamic law constitute an extremely important element of determining law. Despite, its significance and importance, it is often ignored in the policymaking, in the process of legislation related to the public interest. Perhaps this is due to the lack of knowledge of the policy makers of the importance of objective of the law, or their tendency of not consulting the experts when formulating a policy. Therefore, this study attempts to highlight the importance as well as the implementation of principles of maqasid shari‘ah in the country’s administration. The study use library research method, hence the data collected from relevant literatures such as journals, books and other related materials are analyzed and conclusion are made. This study concludes that an effective and efficient administration of an Islamic state heavily depends on the application of dynamic principles provided by shari‘ah. Some of these principles are qawa‘id maqasidyyah, jalb al-masalih wa dar’ al-mafasid and fiqh al-awlawiyyat.